Nepotism and Family Owned Business - N. Sugundan, Dr.; RAJA, S.; Gomathi sankar Jaganathan, Dr. (International Journal of Engineering and Technology, 2018)
This study is used to elucidate the various affects that nepotism has on family run business. It shows the results of the ill and unethical practice of nepotism used in human resource activities in the organization and how it hinders growth of the business as well as disrupts the course of actions, using a conceptual framework. It also highlights the fact of voluntary unemployment adopted by individuals due to nepotism and a family owned business background.Â Â